1922
DOI: 10.1080/00034983.1922.11684303
|View full text |Cite
|
Sign up to set email alerts
|

A Parasite ResemblingPlasmodium Falciparumin a Chimpanzee

Abstract: Plate IXThe following observations were made by us on a chimpanzee, Anthropopithecus troglodytes, at Freetown, Sierra Leone. The animal, according to the statement of the owner, had suffered from an attack of dysentery lasting from January ist to January i6th, 1922. It was examined by us on the iith and 12th of Januar\', at SUMMARY A parasite morphologically indistinguishable from P . falciparum was found by us occurring naturally in a chimpanzee in Freetown,West Africa. This parasite appears to be the same as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

1963
1963
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 0 publications
1
32
0
Order By: Relevance
“…Our data show not only that PfEBA-175 prefers Neu5Ac but also that Neu5Gc interferes with this binding, likely explaining why P. falciparum is unable to successfully infect healthy chimpanzees. Conversely, PrEBA-175 strongly prefers Neu5Gc, perhaps explaining why P. reichenowi failed to infect human subjects in old studies (11,12). The impact of merozoite invasion ligands on host species specificity has been confirmed recently in the simian malaria, Plasmodium knowlesi, in which knockout of P. knowlesi DBP-␣, an invasion ligand related to EBA-175, renders that parasite unable to invade human erythrocytes (53).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data show not only that PfEBA-175 prefers Neu5Ac but also that Neu5Gc interferes with this binding, likely explaining why P. falciparum is unable to successfully infect healthy chimpanzees. Conversely, PrEBA-175 strongly prefers Neu5Gc, perhaps explaining why P. reichenowi failed to infect human subjects in old studies (11,12). The impact of merozoite invasion ligands on host species specificity has been confirmed recently in the simian malaria, Plasmodium knowlesi, in which knockout of P. knowlesi DBP-␣, an invasion ligand related to EBA-175, renders that parasite unable to invade human erythrocytes (53).…”
Section: Discussionmentioning
confidence: 99%
“…falciparum and P. reichenowi are two morphologically indistinguishable Plasmodium species that nevertheless exhibit strong host preferences for humans and chimpanzees, respectively (11,12,15). Recent phylogenetic sequence studies have confirmed the genetic distinctness of these species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the origin of P. falciparum as a zoonosis, and the continuing coexistence of humans and apes in West and Central Africa, extensive field studies have failed to detect P. falciparum in wild-living chimpanzees and gorillas (5). Although there are reports of P. falciparum infecting chimpanzees either in certain captive settings (2) or following splenectomy and deliberate transfer of P. falciparum-infected human blood (8)(9)(10), the resulting infections have low parasitemia and are not known to result in malignant tertian malaria, suggesting a host-specific barrier for replete infection. The existence of host-specific barriers within the Laverania subgenus is supported further by the strict host specificity exhibited by ape Laverania parasites in the wild: Plasmodium reichenowi, Plasmodium billcollinsi, and Plasmodium gaboni infect only chimpanzees, and Plasmodium praefalciparum, Plasmodium blacklocki, and Plasmodium adleri are restricted to gorillas (3)(4)(5)(6).…”
mentioning
confidence: 99%
“…There is also evidence of intrauterine or transcolostral transmission [290,589,819]. Fatal cases of strongyloidiasis have been reported in the chimpanzee, gibbon, orangutan, patas monkey, and woolly monkey [50,51,171,176,228,360,422,504,526,571,636,650,677,857,861].…”
Section: Strongyloidiasismentioning
confidence: 99%